Manipulating Optical Properties of ZnO/Ga:ZnO Core-Shell Nanorods Via Spatially Tailoring Electronic Band Gap - Zhao, Xin (2016)
Enhancing optical and electrical properties of ZnO nanostructures via surface doping is demonstrated by Ga:ZnO–ZnO core–shell nanorods, which are grown by a genetic two-step method. Low-temperature photoluminescence and X-ray photoelectron spectroscopy prove the n + shell significantly suppresses the surface-related recombination by spatially modulating the electronic band structure. The study provides a significant physical insight in designing optoelectronic devices.